1991
DOI: 10.1007/bf00119685
|View full text |Cite
|
Sign up to set email alerts
|

Didactic use of concept mapping in higher education: applications in medical education

Abstract: This paper describes the use of concept mapping for didactic purposes in higher education at the university level, namely, in medical schools. The f'rrst study involved the use of concept mapping to evaluate students' self learned knowledge of subject matter during their clerkship in a department of surgery. The individually constructed cognitive maps facilitated learning by being used in group discussions with the tutor, to identify correct ideas as well as misconceptions, and to convey the tutor's view, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…While it has been shown that concept maps are an effective method for teaching undergraduates complex science content (Arnaudin et al, 1984;Ault, 1985;Cilburn, 1990;Novak, 1990;Briscoe and LeMaster, 1991;Mahler et al, 1991;Markow and Lonning, 1998;McClure et al, 1999;Rebich and Gautier, 2005), the use of this tool as an aid to researchers seeking to find effective ways to make their work accessible to a broader audience has to date not been investigated. In addition to reducing the overall number of concepts, the map is organized in a more hierarchical manner Informal education audiences (using experts in informal science education as proxies) undergraduate students (both science and nonscience majors) *Third-party audience (5-40 people) types were chosen for either their relative closeness in age to the graduate students (e.g., undergraduates or high school students) or the fact that both the faculty and the graduate students were unlikely to have worked extensively with them (e.g., nonscientists in informal education settings such as museums, aquariums, science centers, or in non-graded after-school programs).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been shown that concept maps are an effective method for teaching undergraduates complex science content (Arnaudin et al, 1984;Ault, 1985;Cilburn, 1990;Novak, 1990;Briscoe and LeMaster, 1991;Mahler et al, 1991;Markow and Lonning, 1998;McClure et al, 1999;Rebich and Gautier, 2005), the use of this tool as an aid to researchers seeking to find effective ways to make their work accessible to a broader audience has to date not been investigated. In addition to reducing the overall number of concepts, the map is organized in a more hierarchical manner Informal education audiences (using experts in informal science education as proxies) undergraduate students (both science and nonscience majors) *Third-party audience (5-40 people) types were chosen for either their relative closeness in age to the graduate students (e.g., undergraduates or high school students) or the fact that both the faculty and the graduate students were unlikely to have worked extensively with them (e.g., nonscientists in informal education settings such as museums, aquariums, science centers, or in non-graded after-school programs).…”
Section: Introductionmentioning
confidence: 99%
“…In this example, the boxes represent the concepts and the ellipses the connections that the student perceives between the concepts. As is evident from the example, concept maps differ from traditional mind-mapping in the explicitness with which the connections between concepts are recorded (Mahler et al 1991;Jonassen et al 1993;Plotnick 1997;Novak 1998;Chularut & DeBacker 2004;Clayton 2006;Hay et al 2008;Novak & Canas 2008). Indeed, Novak and Gowin (1984) argue that the power of concept mapping as a learning and teaching tool lies in this recording since it allows for the development of an understanding of the relationships among different bits of information (All & Havens 1997;Baugh & Mellott 1998;Mueller et al 2002;All et al 2003), and provides opportunities to build on previous knowledge and skills (Baugh & Mellott 1998;Dobbin 2001).…”
Section: Implications For Teaching and Learningmentioning
confidence: 99%
“…Similar context contingency was implied by the validation studies by Markham et al (1994) and Winitzky et al (1994), and the use of concept mapping by Roychoudhury (1992, 1994) for instructional purposes. Also, both the rather idiosyncratic nature of knowledge structures and the general finding that the validity of most educational and psychometric is about moderate (e.g., Hoz et al, 1992) render our validity estimates no exception in the area of construct validation.The findings of the current study, a large aggregate of which were derived through strict and careful application of SConSAT in various domains (Bussiba, 1992;Chacham, 1990;Gonik, 1990; Gurfinkel, 1990;Hoz et al, 1990;Mahler et al, 1991;Pomson, 1994;Tomer, 1989;Zellermayer & Hoz, 1995; Pomson & Hoz, in press), support our generalization that the particular dimensions of knowledge that are derived by the analysis of cognitive maps have rather good reliability and validity. These findings and those regarding the edumetric validity of cognitive mapping have four practical implications for researches and teachers.…”
mentioning
confidence: 98%
“…These dimensions of cognitive structure are not or cannot be obtained from concept maps yielded by these versions of concept mapping. Our analysis scheme provides for additional dimensions of cognitive structure (Hoz et al, 1990;Mahler et al, 1991;Pomson, 1994;Zellermayer & Hoz, 1995; Pomson & Hoz, in press).The following 16 concepts were amongst the most central to the course content: base level, caverns, coastal zone, equilibrium/balance, flood plain, fluvial system, glacial landscape, intake area, lateral erosion, maturity, river terraces, seepage, slide, slope, solution, and vertical entrenchment. They were used satisfactorily in an earlier study (Hoz, Kozminsky, & Bowman, submitted).…”
mentioning
confidence: 99%
See 1 more Smart Citation